Natural Variation in Vitamin B1 and Vitamin B6 Contents in Rice Germplasm - Mangel, Nathalie; Fudge, Jared B.; Gruissem, Wilhelm; Fitzpatrick, Teresa B.; Vanderschuren, Hervé (Frontiers in Plant Science, 2022)
Insufficient dietary intake of micronutrients contributes to the onset of deficiencies termed hidden hunger — a global health problem affecting approximately 2 billion people. Vitamin B1 (thiamine) and vitamin B6 (pyridoxine) are essential micronutrients because of their roles as enzymatic cofactors in all organisms. Metabolic engineering attempts to biofortify rice endosperm — a poor source of several micronutrients leading to deficiencies when consumed monotonously — have led to only minimal improvements in vitamin B1 and B6 contents. To determine if rice germplasm could be exploited for biofortification of rice endosperm, we screened 59 genetically diverse accessions under greenhouse conditions for variation in vitamin B1 and vitamin B6 contents across three tissue types (leaves, unpolished and polished grain). Accessions from low, intermediate and high vitamin categories that had similar vitamin levels in two greenhouse experiments were chosen for in-depth vitamer profiling and selected biosynthesis gene expression analyses. Vitamin B1 and B6 contents in polished seeds varied almost 4-fold based on HPLC analyses. Genes encoding select vitamin B1 and B6 biosynthesis de novo enzymes (THIC for vitamin B1, PDX1.3a–c and PDX2 for vitamin B6) were differentially expressed in leaves across accessions contrasting in their respective vitamin contents. These expression levels did not correlate with leaf and unpolished seed vitamin contents, except for THIC expression in leaves that was positively correlated with total vitamin B1 contents in polished seeds. This study expands our knowledge of diversity in micronutrient traits in rice germplasm and provides insights into the expression of genes for vitamin B1 and B6 biosynthesis in rice.